The Use of Low-frequency Active Channel Signals in an Information Leakage Detection and Prevention Systems - A. V. Mamaev (Безопасность информационных технологий, 2011)
This article describes a solution for the protection of the temporary lifting of control over the target machine, while using information leakage detection and prevention systems. It is proposed to use a specially designed channel for alert’s signals through the computer’s power supply.